2003
DOI: 10.1002/cncr.11232
|View full text |Cite
|
Sign up to set email alerts
|

Can patient selection for bladder preservation be based on response to chemotherapy?

Abstract: BACKGROUNDNeoadjuvant chemotherapy for patients with muscle‐invasive bladder carcinoma is given to treat micrometastases and to preserve the bladder. The objective of this study was to evaluate the possibility of bladder preservation in patients with muscle‐invasive bladder carcinoma who were treated with neoadjuvant methotrexate, vinblastine, doxorubicin, and cisplatin (M‐VAC) chemotherapy.METHODSOne hundred four consecutive patients with T2–T4,N0,M0 transitional cell carcinoma of the bladder were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(65 citation statements)
references
References 27 publications
2
53
0
10
Order By: Relevance
“…These results gave support to the idea that first-line chemotherapy could not only improve survival but select responsive patients for bladder preservation [11,12].…”
supporting
confidence: 60%
“…These results gave support to the idea that first-line chemotherapy could not only improve survival but select responsive patients for bladder preservation [11,12].…”
supporting
confidence: 60%
“…52 The advantages of bladder preservation include less surgery, no need for urinary diversion, and preservation of sexual function, all of which presumably contribute to a better quality of life; the debate is whether bladder preservation can occur while obtaining the same survival rates that are achieved with radical cystectomy. 210 TURBT alone can be an alternative treatment strategy for muscle-invasive bladder cancer. In Herr et al, a repeat TURBT found residual tumor in 78% of patients diagnosed with T2 tumors; the 22% of patients without residual tumor were followed conservatively, and the 4% with Ն T3 lesions were treated with chemotherapy.…”
Section: Bladder Preservationmentioning
confidence: 99%
“…In terms of candidate selection, induction CRT would permit more MIBC patients to meet rigorous criteria for PC. To date, a small number of groups have reported their experience with small cohorts of selected MIBC patients treated with PC as a consolidative therapy after induction systemic chemotherapy 72 or low-dose radiotherapy 73 (Table 3). Series of PC after induction chemotherapy alone or low-dose radiotherapy alone showed similar survival and bladder cancer recurrence rates compared with upfront PC series, suggesting that such induction Selective bladder preservation for MIBC therapies are no more likely to improve oncological outcomes of PC for patients selected according to stringent criteria.…”
Section: Pc As Consolidative Therapy After Induction Crt: the Tmdu Prmentioning
confidence: 99%